2017
DOI: 10.3390/ijms18112420
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Targeted Therapies for Epidermal Growth Factor Receptor and Its Resistance Mechanisms

Abstract: Cancer therapies targeting epidermal growth factor receptor (EGFR), such as small-molecule kinase inhibitors and monoclonal antibodies, have been developed as standard therapies for several cancers, such as non-small cell lung cancer, colorectal cancer, pancreatic cancer, breast cancer, and squamous cell carcinoma of the head and neck. Although these therapies can significantly prolong progression-free survival, curative effects are not often achieved because of intrinsic and/or acquired resistance. The resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 158 publications
(178 reference statements)
1
92
0
1
Order By: Relevance
“…S1). This is important as Her2 is known to interfere EGFR internalization and RNA‐seq data from 28 dog bladder tumors ( vs . 4 normal urothelial layer) indicated that Her2 was enriched in dog bladder tumors in these animals (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1). This is important as Her2 is known to interfere EGFR internalization and RNA‐seq data from 28 dog bladder tumors ( vs . 4 normal urothelial layer) indicated that Her2 was enriched in dog bladder tumors in these animals (Supporting Information Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since internalization of EGFR complexes plays an important role in the success of these targeted agents, the presence of EGFR internalization‐impairing mutations or upregulation of Her2/neu (known to interfere with EGFR endocytosis) are among the factors known to impair the efficacy of EGF‐based strategies …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some portion of the larger observed variability, in PK exposure for example, will be related to the route of administration because cytotoxic agents are most typically delivered intravenously whereas targeted therapeutics are often administered orally. The consequences of large variability in exposure across patient populations are the risk of (i) poor efficacy due to subtherapeutic exposure, (ii) unpredictable toxicity and adverse events associated with higher than optimal concentrations, and (iii) the development of drug resistance caused by inconsistent or inadequate tumor exposure . To best understand the disposition of a molecularly targeted therapy, it is important to evaluate the degree of interindividual variability of PK parameters in patients with cancer.…”
mentioning
confidence: 99%
“…patient populations are the risk of (i) poor efficacy due to subtherapeutic exposure, (ii) unpredictable toxicity and adverse events associated with higher than optimal concentrations, and (iii) the development of drug resistance caused by inconsistent or inadequate tumor exposure. 4,5 To best understand the disposition of a molecularly targeted therapy, it is important to evaluate the degree of interindividual variability of PK parameters in patients with cancer.…”
mentioning
confidence: 99%